Guineensis Nursery Sdn Bhd - Kawang, Wilfred; Andrews, Anselm Aldelm; William, Steffeny Martinna; Jinis, Rufina; Galigeh, Eashter (2013)
Oil palm is the main commodity of Malaysia. Oil palm plantation is also the main source of income of Malaysia since few years ago. Thus, oil palm plantation should be increased due to the increase of consumer around the world. GUINEENSIS NURSERY Sdn. Bhd. is a company that will cooperate with Sime Darby Sdn. Bhd in the production of very high quality of CALIX 600 clone oil palm seedling for Sime Darby Sdn Bhd themselves. We are ordering germinated oil palm seed from Sime Darby Sdn. Bhd and nourish it in our nursery with a high quality maintenance in order to produce high quality of seedlings and to fulfill the unlimited needs. We have only one nursery that located at Merotai Tawau. Our product will be sold to Sime Darby Sdn. Bhd according to the company's agreement. We are striving to be the main supplier of CALIX 600 clone of oil palm seedling for Sime Darby Sdn. Bhd for their plantation in Tawau and Kunak. The strength which this business will possess is we have the contract of business coorporation with Sime Darby Sdn.Bhd. We are also have the ability to change with the times and the low cost of raw materials in terms of production. Rather than limiting the future opportunities by having a small area, GUINEENSIS NURSERY Sdn Bhd will have 6 hectares of land for the flexibility in production. GUINEENSIS NURSERY Sdn. Bhd will be operated as a Partnership Agreement. The total needed capital of GUINEENSIS NURSERY company is RM200,000. Partnership cash contribution is RM24,000. The amount needed in loans is RM8313,599. The capital will be used for office building RM25000, raw materials RM25,282,45, and operation RM35,828.45.